Proses Produksi Katalis NaOH/CaO/y-Al²O³ dengan Metode Impregnasi untuk Pembuatan Biodiesel - Agusliana, Sari (Jurnal Penelitian Multidisiplin Ilmu, 2024)
Utilization of Eggshell Catalyst in the Preparation of Biodiesel from Coconut Oil .The decline in petroleum reserves in the world from year to year has decreased, which has an impact on increasing prices for fossil fuels and their derivatives. Eggshell waste from controlled combustion at high temperatures will produce chemical compounds, one of which is CaO, which can be utilized for various chemical processes including as a catalyst. The purpose of this study was to determine the effect of NaOH/CaO/?-Al2O3 catalyst on the acquisition of biodiesel. The production of biodiesel using NaOH/CaO/?-Al2O3 solid catalyst was produced by impregnation method using a furnace at 900°C for 6 hours.